PENGUJIAN TARIK KOMPOSIT SPESIMEN CAMPURAN SERAT PISANG ALUR DIAGONAL DAN PASIR BESI DENGAN MATRIK RESIN POLYESTER DENGAN METODE HAND LAY-UP - Nicolaus Ardi Kurniawan; Ferry Setiawan; Edi Sofyan (Sekolah Tinggi Teknologi Kedirgantaraan, 2022)
Composite is a material formed from a combination of two or more constituent materials through an inhomogeneous mixture, where the mechanical properties of each constituent material are different. Composite materials generally consist of two elements, namely fiber as a filler material and a matrix as a fiber binding material which is formed on a macroscopic scale and physically fused. The word composite is an adjective which means an arrangement or combination. This research was designed with several composite materials using banana midrib fiber reinforcement, iron sand, and polyester resin as the matrix with the hand lay up method. This research can be a reference for the manufacture of structures on the cross section of unmanned aircraft, ships, brake linings. Experimental method is the method used in this study by making a composite from a mixture of banana fiber and iron sand which aims to determine the characteristics of the best specimens from the variety of specimens that have been made. By performing a tensile test on four specimens (empty, low, medium, hight) with four variations of the matrix 100%, 80/10/10, 70/15/15, 60/20/20, the lowest stress value was obtained in the specimen. high (9,905) and the highest in the low specimen (45,267), for the lowest strain value in the low specimen (0,4) and the highest in the empty specimen kosong (2), for the lowest elastic modulus value in the high B specimen (11,005) and the highest in the low specimen. (301,272).